Creativity through retrospection? Software industry projects in Iceland - Auður Guðríður Hafliðadóttir 1990- (2023)
This thesis investigates how creativity emerges in the context of retrospection within Icelandic software organizations. Retrospection is an important part of projects, where individuals and teams learn from their experience on the project. The study aims to explore the relationship between retrospection and creativity in project management by examining the practices and perspectives of software professionals in Iceland. To find answers to how teams within software organizations in Iceland use creativity when it comes to reviewing projects and learning from them. An assessment is made of when there is an opportunity to use creativity in retrospection and how it can be applied. As well as whether retrospection encourages the use of creativity among employees. The culture of the organizations is examined to see if it affects learning and recording of knowledge and the experience within them. Along with examining whether the culture and work environment result in increased use of employees' creativity. The research employs a qualitative approach, using semi-structured interviews to gather data from twelve individuals who work as project managers or performed such work within software organizations in Iceland. The results of the study show that creativity and retrospection come together to various ways and extents. To name a few examples, in the culture, in communication, when changes or problems arise during retrospection, and during the final retrospection and documentation. It is important that project managers promote an open culture and communication when conducting retrospection, so all individuals have an equal chance to express their opinion and can embrace their creative side. The study seeks to contribute to the existing literature on creativity in project management by exploring the role of retrospection in fostering creative thinking and problem solving. The findings of this research can potentially inform project management practices in software organizations and contribute to a better understanding of ...